PREFERENSI PAKAN DAN PERTUMBUHAN ANAKAN BULUS (Amyda cartilaginea Boddaert, 1770) DI PENANGKARAN PT. EKANINDYA KARSA, KABUPATEN SERANG, BANTEN - Fatwa Nirza Susanti; Mirza D. Kusrini; Achmad Machmud Thohari (Media Konservasi, 2016)
Softshell turtle (Amyda cartilaginea Boddaert, 1770) is categorized as Appendix II CITES and vulnerable in IUCN Red List Data Book. Captive breeding of this turtle is important to continue their sustainable utilization. PT Ekanindya Karsa was one of the pioneers in captive breeding of this species since 2008. Until now, reference related to management and maintenance techniques of softshell turtle in captivity are few. This research aims to analyse feeding preferences in juveniles. The results will assist wildlife conservation efforts and improve captive breeding effort for the future. Research was carried out at PT. Ekanindya Karsa from July to October 2012. Fifteen juveniles were given food for 9 weeks comprises of tuna, shrimp, spinach and sweet potatoes with cafeteria methods. Based on the number of food intake and cost efficiency, prefereed food was sweet potato and tuna. Feeding activities were visible in the morning (7.00 – 10.00 am) and evening (7.00 – 10.00 pm) with ad libitum sampling methods. During experiment, all growth parameter (curve carapacea length, curve carapacea width and body mass) increased constantly.Keywords: food preference, growth, juvenile, PT. Ekanindya Karsa, softshell turtle.